AN ANALYSIS OF THE IMPACT OF WATCHING YOUTUBE VIDEOS OF NATIVE CONTENT CREATORS ON STUDENTS’ ENGLISH SPEAKING - Rustan, Nilasari; Muliati, A.; Farahdiba, Syarifah (Universitas Negeri Makassar, 2025)
This research analyzes the impact of watching YouTube videos created by native content creators on students’ English pronunciation, fluency, vocabulary, and confidence. The study investigates how exposure to authentic language use influences these key aspects of speaking. Using a qualitative case study with elements of descriptive research and phenomenology, data were collected through interviews and focus group discussions with five students from the English Education program who regularly engage with native content on YouTube. The findings suggest that consistent exposure to native speakers through YouTube videos significantly improves students' pronunciation accuracy and enhances their fluency in spontaneous speech. Additionally, participants reported a deeper understanding of conversational nuances and cultural references, which contributed to their overall confidence in English communication. This study highlights the effectiveness of YouTube as a self-directed learning tool and its potential to complement traditional language learning methods.